Trade in healthcare and health insurance services: WTO/GATS as a supporting actor (?) - Rudolf Adlung (Intereconomics, 2010)
The General Agreement on Trade in Services (GATS) is far broader in policy coverage than conventional trade agreements for goods. At the same time, governments are offered more flexibility to tailor their obligations to sector- or country-specific needs. As a result, commitments vary widely across sectors and modes of supply. Health insurance has proved far more popular, for instance, than healthcare services. Surprisingly, governments have been less selective in other policy contexts, in particular bilateral investment treaties (BITs). Many signatories of such treaties, including individual EU Members, have undertaken potentially challenging obligations across virtually all service sectors. Yet, though frequently invoked, BITs do not meet the same standards, in terms of transparency, open (consensual) rulemaking and legal certainty, as commitments under the GATS.
Keywords: 330